Primary Accounting of Non-Current Assets Held for Sale - ShygunM. М.; Mychak, N.O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The article is devoted to the study of the documentary support for operations with non-current assets held for sale. The importance of the study is determined by the fact that in the Ukrainian business accounting and recording practice, information about economic transactions with non-current assets held for sale is recorded in the forms approved for fixed and intangible assets that do not reflect all the aspects of accounting for non-current assets held for sale, which is inappropriate because it does not allow for their rational management and control. Despite the judiciousness of studies on recording of transactions with non-current assets, recording of transactions with non-current assets held for sale needs further studies because it is not sufficiently developed nowadays. Absence of special documentary support for accounting of non-current assets held for sale is emphasized. The article’s aim is to develop recommendations for improving the documentary support for transactions with non-current assets held for sale taking into account the economic substance and legal specifics of such transactions. The authors propose a form of the Act on reclassification of non-current assets into non-current assets held for sale, which can provides a substantiated documentary confirmation of the execution of such transactions. This form takes into consideration all the necessary information about recognition of an asset as one held for sale. The authors’ recommendations are given. In order to improve the recording of transactions with non-current assets held for sale, the primary documents should be issued not only at the moment of such assets reclassification, but also prior to their reclassification from non-current assets into non-current assets held for sale, and in the period of holding them for sale till the moment of transfer to the buyers.